(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Primulina lechangensis (Gesneriaceae), a new species from northern Guangdong province in southern China is described and illustrated. Its morphology suggests affinities to P. longicalyx, but can be distinguished from similar taxon by several distinct characters including: smaller leaf blade (2.0-3.5 × 1.0-1.2 cm), base cuneate-attenuate; smaller bracts (1.0-1.5 × c. 0.15 cm); shorter calyx lobes (0.8-0.9 cm long) tuberculate inside; smaller corolla tube (c. 2 cm long), inflated in the middle and contracted near the mouth; shorter glabrous filaments (0.3-0.4 cm long), inserted 1.3-1.5 cm from base of corolla; stamens and staminodes glabrous; pistil 1.4-1.5 cm long, and capsule c. 1.5 cm long. This species is further exemplified by photographs, and a distribution map is presented. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21359 Bangladesh J. Plant Taxon. 21(2): 187-191, 2014 (December)